The Effect of Problem Based-Learning Based on Science Edutainment on Students’ Logical Thinking - Ariefka, Reza; Sari, Sasmita (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
The problem-based learning model based on science edutainment, presents a problem in each concept of game-based material. The main characteristic of the learning model used in this study is using games to help students understand problem-based material in an entertaining way. This study aimed to examine the effect of the problem based-learning based on science edutainment in scientific content on students’ logical thinking. The type of research used in this research is quantitative research. This study had conducted in class IV of 45 students at SD Negeri Buay Pemaca. Data collection techniques included interviews, observation, documentation, and tests. Based on statistical tests, the independent sample t-test showed a significant value of 0.000 > 0.05, meaning that the science edutainment problem based-learning model had influenced students' logical thinking. The conclusion of this study is that the problem-based learning model based on science edutainment in science lessons has an effect on the logical thinking abilities of fourth grade elementary school students.